Structural health monitoring using advanced contact and contactless technologies - Zhao, Dongyu (2017)
Smart materials based structural health monitoring (SHM) has been in use for few decades, where the sensors need to be in contact with the host structure under investigation. Especially sensors such as fiber optical sensors, piezoelectric sensors need contact with the host structure under investigation. However, a recent metamaterial based SHM technology can be used both as a contact and contactless method. This project applied electromagnetic metamaterial such as localized surface plasmon (LSP) and metamaterial waveguides (SPP) to monitor several different specimens such as aluminum hollow section, shell, cone, concrete blocks, steel beam, bicycle tires, metallic steel pipe, and water channels to explore material’s potential on SHM field. The smart materials can be either surface bonded on or placed at a significant distance away from the specimens. These experiments were conducted using a vector network analyzer and a robotic arm scanner. As this is the first Final Year Project relative to metamaterial SHM in NTU, the experiments are designed both fundamental and innovative. The experiment results are observed as S21 transmission signal form and then statistically evaluated using root mean square deviation (RMSD).